ESPECIES DE ORIBATIDA (ACARIÑA, CRYPTOSTIGMATA) ASOCIADAS A ESPECIES DE PLANTAS, EN QUEBRADAS CON VEGETACIÓN DE NEBLINA DE LA PROVINCIA DE ANTOFAGASTA, CHILE - Covarrubias, Rene; Toro, Haroldo (Acta Entomológica Chilena, 2022)
The Oribatid fauna (Cryptostigmata, Acariña) in soils under 17 plant species and bare soils, in the Paposo ravines and surrounding areas (25°00’ S; 70°26’ W) was studied. The biota is of a desert type, with a main influence of the fog, coming from the sea. Sixteen Oribatid species were found, among which one new genus and two new species that are described elsewhere; also a new subspecies is proposed here: Zygoribatula bonairensis chilensis. Three species had not been mentioned before neither for Chile ñor for the Neotropical Región; 7 other species are mentioned for Chile for the first time. A total of 254 samples were taken, from 1993 to 1996, and treated in Berlese-Tullgren funnels; for all samples every individual was counted and classified to the species level. A quantitative analysis was performed with the data of those species with high sample frequency and high abundance. Two groups of oribatid species were clearly separated. One group was formed by five species of primitive cosmopolitan oribatids, which were present in a high percentage of the samples (>70%), with mean total densities between 22 and 241 individuals/1000 cc of soil, presenting numerous preadult forms and that were found in soils under most plant species. The second group, with ten species, were represented mostly by few individuáis and with no immature forms, inelude neotropical and probably endemic species, present in soils under 1 to 3 plants only. A special case is an aquatic Hydrozetidae, cosmopolitan, found associated to Cotula coronopifolia in a very small and isolated pond. Quantitative data are given for the abundance of each species; in the first group, two way analysis of variance were performed to test the influence of the plant species factor and the sampling date factor on their abundance. A two entries contingency table is given for the co-ocurrence of each oribatid species and each plant species or bare soil; the latter surprinsingly presenting up to 6 oribatid species.